Notched graphite under multiaxial loading - S.M.J. Razavi; M. Peron; J. Torgersen; F. Berto (Fracture and Structural Integrity, 2017)
Cylindrical specimens made of polycrystalline graphite and weakened by circumferential V-notches under mixed mode I/III loading were studied in this research. Different geometries of V-notches varying the notch opening angle and the notch tip radius were tested. Appling various ratios of tensile and torsion loads, the multiaxial static tests have been conducted. Averaged Strain Energy Density (ASED) criterion previously presented by the same authors is employed here for the case of tension and torsion loadings applied in combination. The fracture behavior of the tested joints under multiaxial loading has been successfully predicted using the ASED criterion.